Evaluation of lamb production potentiality of the Barind, Jamuna river basin and coastal region sheep of Bangladesh under intensive management - Ahmed, Sadek; Rakib, Md. Rezaul Hai; Yesmin, Morsheda; Sultana, Nasrin; Jahan, Nusrat; Ershaduzamman, Md. (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study was conducted to investigate the lamb production potentiality in terms of nutrient intake and utilization, growth performances, carcass characteristics and meat quality of three regional native sheep under intensive management condition. Materials and methods: A total of 24 growing lambs having 08 lambs from each group with 4 to 6 months of age were used in this study. 40% urea molasses straw (UMS) and 60% concentrate mixture of the total diet were supplied according to lamb body weight. The total feed was offered at 4.0% live weight on dry matter basis of each animal. The completely randomized design was used in this experiment. Results: The dry matter intake was significantly (P<0.01) lower but DM, OM, CP and ADF digestibility were higher (P<0.01) in Jamuna river basin group compared to other groups. All group having positive N-balance but significantly higher value (P<0.01) observed in Barind region sheep. Lower FCR (P<0.01) was found in Jamuna river basin group but it not differ significantly with Coastal group. Nevertheless, daily gain and total live weight gain were significantly (P<0.01) higher in Costal sheep. However, cost per kg gain, dressing percent, carcass characteristics and nutritive value of meat did not differ among the groups. Conclusion: All the regional sheep have the potentiality but coastal region sheep are more potential than other regional sheep for commercial lamb production in Bangladesh. The results of this study could be exploited by disseminating this to the wider stakeholders to develop entrepreneurship mechanism on sheep farming. http://doi.org/10.5455/javar.2018.e243